Evaluasi Surveilans Respons Cepat Krisis Kesehatan Akibat Wabah: Literatur Review - Angraeni, Fitri; Jannah, Wirdatul; Wasir, Riswandy (Jurnal Khazanah Intelektual, 2025)
Introduction: Outbreaks remain one of the biggest public health challenges today. The prevention and control of diseases with outbreak potential depends on the effectiveness of a successful response system with the help of surveillance activities. The aim of this study was to determine the evaluation of surveillance in rapid response to health crises due to disasters and outbreaks. Methods: This study used the literature review method, which refers to the PRISMA method. Reference searches were conducted on three databases, namely Google Scholar, Science Direct, PubMed. A total of 6 articles were selected based on the inclusion criteria. Results: The results of the literature review show that in the input aspect, most surveillance systems face challenges in the form of limited number and competence of officers, lack of funds, and inadequate facilities and infrastructure. Although the methods and SOPs are standardized, their application is not consistent. In the process component, there are obstacles in collecting and analyzing data and disseminating information that is not yet optimal. As a result, the output of the surveillance system has not met national standards. Conclusion: Strengthening the capacity of human resources, providing financial support and infrastructure, and improving the quality of method implementation and analysis are needed to optimize the health surveillance system in Indonesia Keywords: Evaluation, Surveillance, Outbreaks